Un établissement rural à enclos fossoyé de La Tène C2/D1 en Val de Loire : le site du “ Vivier ” à Saint-Laurent-Nouan (Loir-et-Cher) - Philippe Salé; Marc Gransar; Jean-Philippe Gay (Revue Archéologique du Centre de la France)
In 2008, an excavation was conducted over near 42 000 square yards at Saint-Laurent-Nouan (Loir-et-Cher), in the Loire valley. Several sites were identified but only the La Tène C2 to the beginning of La Tène D1 finds will be considered in the present paper. They are related to a rural settlement materialized by five houses and four attics in three distinct spaces enclosed within a large ditch. The study of the site reveals a very modest settlement which perfectly fits with the corpus of Iron Age enclosed sites known in the Center of France.